PENDAMPINGAN MASYARAKAT DALAM UPAYA MENINGKATKAN KESADARAN HUKUM TENTANG HAK MILIK ATAS TANAH MELALUI SISTEM PENDAFTARAN TANAH DI DESA ANDAMAN KECAMATAN ANJIR PASAR KABUPATEN BARITO KUALA - Hanafi; Nahdhah; Muhammad Syahrial Fitri (Jurnal Pengabdian Sumber Daya Manusia, 2021)
The development is getting more advanced, placing land in an important aspect in society which is increasingly dynamic as it is today, so that legal certainty is an important factor. We will get the terms of ownership if we register a plot of land in question with the government. There are several ways of registering land that we can take, namely, "systematic registration" and "sporadically". Systematic land registration is based on a work plan and is carried out in areas stipulated by the minister, while sporadically is carried out at the request of interested parties. Due to the lack of community legal awareness regarding the importance of land ownership through the land registration system in Andaman Village, Anjir Pasar Subdistrict, Barito Kuala Regency, it can be seen from the data we collect that only a few people have proof of land ownership in the form of certificate or just a seal. Various factors caused him to be less aware of this, including the problem of costs that must be incurred during the management process and also the perception that the bureaucratic process at BPN is difficult. The purpose of this service is to provide assistance to the community in order to increase the understanding and legal awareness of the Andaman Village community of their land rights through the land registration system, so that the land they own gets legal certainty and can be used as a legal basis when a land dispute occurs. In addition, with this assistance, the Andaman Village apparatus, through its government apparatus, can form a special work unit to receive reports from the community who wish to register their land and make an inventory of lands that have not been registered in the certificate of ownership together with the Extension Team in this community service program. This certainly made it very easy for BPN to conduct field surveys as well as to obtain data on the “free certificate” program which is currently being carried out by the government. Apart from being able to be used as a clear legal basis when a dispute occurs, the existence of a certificate can be used as a loan guarantee in the financial sector, this will certainly bring the productivity value of the people in Andaman Village, where the majority of the population is farming, such as buying fertilizers, agricultural tools, even for increase their agricultural land. This of course also has an impact on increasing the income and welfare of the farming community.